Evaluating the bioequivalence and safety of liraglutide injection versus Victoza® in healthy Chinese subjects: a randomized, open, two-cycle, self-crossover phase I clinical trial - Liu, Chao; Xu, Hongrong; Yuan, Fei; Chen, Hanjing; Sheng, Lei; Chen, Weili; Xie, Haisong; Xu, Hongmei; Li, Xuening (Frontiers in Pharmacology, 2023)
Liraglutide is an acylated glucagon-like peptide-1 (GLP-1) analog, as a GLP-1 receptor (GLP-1R) agonist, its pharmacokinetic and pharmacodynamic properties make it an important therapeutic option for many patients with type 2 diabetes mellitus. This study compared the bioequivalence and safety of liraglutide with the originator product in healthy Chinese adult subjects.Methods: Subjects (N=36, both sexes) were randomized in a 1:1 ratio into 2 groups (18 cases each) for a two-cycle, self-crossover trial. Each cycle involves a single subcutaneous injection of the test and reference drugs, with an washout period of 14 days. The plasma drug concentration was quantified by liquid chromatography tandem mass spectrometry (LC-MS/MS). The main pharmacokinetic parameters were statistically analyzed to assess drugs bioequivalence. Also, the safety of the drugs was assessed throughout the trial.The geometric mean ratios of Cmax, AUC0-t and AUC0-∞ were 103.73%, 103.01% and 103.03%, respectively, and the 90% confidence intervals (CIs) were consistent with the range of 80.00% to 125.00%, indicating that the two formulations had similar pharmacokinetics. Meanwhile, safety results showed both drugs were well tolerated.: Studies have shown that the test drug has similar bioequivalence and safety to the reference drug. Clinical trial registration: [http://www.chinadrugtrials.org.cn/index.html], identifier [CTR20171303].